2007
DOI: 10.1002/cncr.23165
|View full text |Cite
|
Sign up to set email alerts
|

Late recurrence from salivary gland cancer

Abstract: BACKGROUND.The purpose of the current study was to determine the incidence of late recurrences, which were defined as those occurring ≥5 years after initial therapy, among patients treated for salivary gland cancer.METHODS.Between 1960 and 2000, 145 patients underwent definitive therapy for localized carcinomas of the salivary glands and were clinically without evidence of disease at 5 years of follow‐up. Cumulative probabilities for developing a subsequent late recurrence were estimated using the Kaplan‐Meier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 24 publications
2
41
0
Order By: Relevance
“…With anecdotal knowledge of patients who experienced late relapses, oncologists may not consider 5-year-and sometimes even 10-year-survival rates to adequately predict whether a specific patient is cured. 7,8 Nonetheless, in the cases that were presented in this survey, close to 90% of clinicians indicated that certain patients were cured 20 years after treatment. It is unclear whether the clinicians would have told the patients in these case studies that they are cured.…”
Section: Discussionmentioning
confidence: 84%
“…With anecdotal knowledge of patients who experienced late relapses, oncologists may not consider 5-year-and sometimes even 10-year-survival rates to adequately predict whether a specific patient is cured. 7,8 Nonetheless, in the cases that were presented in this survey, close to 90% of clinicians indicated that certain patients were cured 20 years after treatment. It is unclear whether the clinicians would have told the patients in these case studies that they are cured.…”
Section: Discussionmentioning
confidence: 84%
“…[11][12][13] However, beneficial effect of postoperative treatment on survival is less clear, partly because successful surgical salvage is frequently possible after locoregional failure and also because survival is related to the high risk for development of distant metastasis, which may be unrelated to locoregional control. Postoperative radiation has been reported to improve locoregional control and is, therefore, commonly used for most cases excepting the very early lesions resected with clearly adequate margins and absence of perineural invasion.…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to investigate possible association between formation of new blood vessels and development of metastasis in salivary gland tumors, the present work investigated the most frequent of these lesions (PA) as a conceptual standard for non-metastasizing disease, as well as three of the most important malignant neoplasms for which metastasis is possible, but less (PLGA) or more (ACC, MEC) frequent [16,17]. These lesions also diverge regarding to differentiation and myoepithelial content [18].…”
Section: Discussionmentioning
confidence: 99%